Strategic issues of development of the manufacturing industry in the Republic of Kazakhstan - Tasbulatova, D.S.; Toksanova, A.N.; Galiyeva, A.Kh. (BUKETOV BUSINESS REVIEW, 2019)
In this article the relationship of industry with other economic categories is considered, providing a basic analysis of support programs offered annually in the Messages of the President of the Republic of Kazakhstan. The main problem of studying issues related to the manufacturing industry is explained by the fact that through reproduction new technologies are always created, which often contribute to the growth of other sectors of the economy. New strategies for the manufacturing industry will increase the exports of manufactured domestic products, which mean export growth in the manufacturing industry. In the work the problem of the analysis of trends of development of a segment of manufacturing industry is investigated, the factors of growth of branches of the mechanical engineering defining innovative-technological development and provision of the transition to a new level of industrial production are defined. The structure of preindustrial cycle is considered, the tendencies of innovative growth and adequate strategy of development are analyzed. The analysis of programs of state support of industrial production is given taking into account the factors of forms of the organization and type of strategy of innovative-technological development.